Quantitative and Qualitative Characteristics of Forage in the Sorghum (Sorghum bicolor L. Moench) and Berseem Clover (Trifolium alexandrinum L.) Intercropping Systems - Naghme Ashoori (University of Tabriz, 2021)
Background and Objective: This study was conducted to evaluate the forage yield and quality in the additive and replacement series of sorghum and Berseem clover intercropping.